Aflasafe products protect maize and groundnut from aflatoxin contamination in more than 100,000 hectares in four countries in sub-Saharan Africa - CGIAR Research Program on Agriculture for Nutrition and Health (2017)
IITA is implementing strategic partnerships with private companies or Government entities to use Aflasafe products in maize and groundnut fields of four sub-Saharan Africa nations. Over 100,000 ha were treated with Aflasafe during 2017, allowing production of maize and groundnut with safe aflatoxin levels. Large-scale use of Aflasafe contributed to improve food safety [e.g. in Nigeria 91% of samples had less than 20 ppb] and increased the income of smallholder maize farmers (average 11.5% more than regular maize).